If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + -2 = 36x + 2 Reorder the terms: -2 + 20x = 36x + 2 Reorder the terms: -2 + 20x = 2 + 36x Solving -2 + 20x = 2 + 36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36x' to each side of the equation. -2 + 20x + -36x = 2 + 36x + -36x Combine like terms: 20x + -36x = -16x -2 + -16x = 2 + 36x + -36x Combine like terms: 36x + -36x = 0 -2 + -16x = 2 + 0 -2 + -16x = 2 Add '2' to each side of the equation. -2 + 2 + -16x = 2 + 2 Combine like terms: -2 + 2 = 0 0 + -16x = 2 + 2 -16x = 2 + 2 Combine like terms: 2 + 2 = 4 -16x = 4 Divide each side by '-16'. x = -0.25 Simplifying x = -0.25
| n^2+8n-7=0 | | 7w^2+3=-10w | | 36=16x-12x | | 4(2x)=40 | | 3x^2+x-0.5=0 | | 2(3x)=36 | | 10x+6y=16 | | -7x^2-18x+0=0 | | 2z-67=-21 | | 8-(-4)+5=12 | | 7n+3-5n=3n-6 | | V=3.14v^2h | | (25)(7)+x=175 | | -3x+6x=0 | | 0=5x^2-64x-13 | | 18+5=48 | | x-29=15 | | .5(12x-8)=9x-18 | | 5x-3-2x=2(x-4) | | 3(x+2)=5(x-1)+5 | | 0=2a^2+7a+3 | | 4(5y-3)-(8y+5)= | | 2x+5(6x-4)=44 | | 40(25+x)=1 | | 8x-14=3x-6 | | m+90=150 | | -16x^2+324=0 | | 9x+6=6x+4 | | 0=-15m^2+60 | | 8(4+x)=360 | | 10x+7=8x-6 | | 21-12=3(x-8) |